2008
DOI: 10.1038/eye.2008.157
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cataract surgical opportunities and complication rates in UK higher specialist training

Abstract: Purpose The volume of cataract surgery performed by trainee ophthalmologists in the UK, and the complication rates experienced by those trainees is unknown. As a result, no appropriate audit benchmark exists for trainees or their trainers. This study describes the surgical opportunities and rates of posterior capsule rupture (PCR) experienced by higher specialist trainees in one UK training region and explores influencing factors. Methods Number of cataract operations and episodes of PCR in each calendar month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
5
9
0
2
Order By: Relevance
“…The overall rate of 2.48% for senior trainees (specialist registrars and fellows) in this study was comparable with that reported in a recent study that analysed UK trainees log books 19 (mean 2.29%, range 0.6-6.9%). The upper end of this range may appear alarming, but with small sample sizes these variations in rates may well be due to sampling error, an effect which is well illustrated by our funnel plots.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The overall rate of 2.48% for senior trainees (specialist registrars and fellows) in this study was comparable with that reported in a recent study that analysed UK trainees log books 19 (mean 2.29%, range 0.6-6.9%). The upper end of this range may appear alarming, but with small sample sizes these variations in rates may well be due to sampling error, an effect which is well illustrated by our funnel plots.…”
Section: Discussionsupporting
confidence: 78%
“…These data contrast with previous studies, which only presented figures for overall PCR rates without any measures of variation between surgeons, 6,8,9 with the exception of a few small studies that focused on trainees alone. 19 Our previous report 9 has demonstrated that the data collected are likely to be typical of all cataract surgery in the United Kingdom, as the basic demographic data on age, sex, and frequency of day case are similar to the National Hospital Episode Statistics during the same time period. 21 As expected, the study demonstrates that the rate of PCR is much lower for independent surgeons (consultants, staff grades, and associate specialists, Figure 2) than it is for senior trainees (specialist registrars and fellows, Figure 3) and the most junior trainee surgeons (SHOs, Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 UK trainees' logbook reviews demonstrate significant decreases in complication rates with increasing experience. 6 One review of 680 trainee operations over four years saw vitreous loss rate halved from 5.1% to 1.9% after the first 80 cases, correlating with significant falls in mean phacoemulsification time. 7…”
mentioning
confidence: 99%
“…1 UK trainees' logbook reviews demonstrate significant decreases in complication rates with increasing experience. 6 One review of 680 trainee operations over four years saw vitreous loss rate halved from 5.1% to 1.9% after the first 80 cases, correlating with significant falls in mean phacoemulsification time. 7 While this indicates '80' as a possible minimum, trainees' efficiency continues improving well beyond this, 7 and complications keep falling after the first 200 cases.…”
mentioning
confidence: 99%